Analysis of Learning Media Needs for Physics of Motion Course Based on Android Platform - Ria Asep Sumarni; Siti Ayu Kumala (Yayasan Insan Mulia Bima, 2024)
Teaching and learning activities in the post-pandemic educational environment are already underway in both schools and universities. However, there are also those who still apply a hybrid learning system, one of which is the learning system at Indraprasta PGRI University which still applies a hybrid learning system, namely the physics of motion course. Utilizing Android-based learning media can enjoy learning experiences, facilitating access to various educational resources. It is important to know the needs of students and educators in the process of learning physics of motion to improve the quality of learning, namely by conducting a needs analysis. The aim of this research is to determine the importance of the need for Android-based motion physics learning media. The method used in the research is exploratory descriptive research. From the results of observations and interviews conducted with several motion physics lecturers and observing learning activities in class, the methods used in learning still use classical methods. Learning the physics of motion using Matlab requires a video guide so that it is easy for students to understand. From the results of filling out the questionnaire via a questionnaire, it can be concluded that the results of the analysis of students' needs for Android learning media in the physics of motion course showed that 88.31% answered that they agreed with the development of an Android-based motion physics learning application. So it can be concluded that the development of Android-based motion physics learning media is needed by Informatics Engineering students at Indraprasta PGRI University.